Burned-Out Testicular Tumors in Adolescents: Clinical Aspects and Outcome - Giorgio Persano; Alessandro Crocoli; Maria Debora De Pasquale; Raffaele Cozza; Rita Alaggio; Francesca Diomedi Camassei; Federico Beati; Pierluigi Di Paolo; Cristina Martucci; Alessandro Inserra (Frontiers Media S.A., 2021)
Purpose: Testicular germ cell tumors are the fourth most common neoplasm in adolescents, accounting for 8% of all tumors in the age group 15-19 years. On rare instances, the primary testicular lesion is not clinically or radiologically evident while nodal or visceral metastases represent the clinical manifestations of the disease. This phenomenon is described as "burned-out testicular tumor." In this paper, the authors report a single-institution experience with burned-out testicular tumors in adolescents and discuss their clinical implications.Patients and Methods: All the patients diagnosed with metastatic testicular germ cell tumors at Bambino Gesù Children Hospital between January 1, 2010, and June 30, 2020, were included in the study. Patients were categorized into two groups: "primary testicular" and "burned out." All the patients were staged and treated according to the AIEOP-TCGM 2004 protocol.Results: Eleven patients were classified as "primary testicular," and five patients were classified as "burned out." "Burned-out" tumors were associated with the presence of systemic symptoms compared to "primary testicular" tumors (80 vs. 0%; p = 0.0027) and higher aFP, hCG, and LDH levels (p < 0.00001). The "burned-out" population had a statistically significant higher incidence of relevant toxicity than the "primary testicular" population (80 vs. 18%; p = 0.0357) and a worse outcome in terms of both mean overall survival (15 vs. 43 months; p = 0.0299) and mean event-free survival (12 vs. 38 months; p = 0.0164).Conclusion: "Burned-out" testicular tumors seem to be a well-distinct clinical entity with a high treatment-related toxicity and poor prognosis. Further studies are needed to clarify the "burned-out phenomenon" and to identify more effective therapeutic strategies for these patients.